Development of Long Line Board Media for Creative Thinking in Class IV Elementary School Students - Fitria Rahmawati; Mulyawati, Ima (Universitas Ma'arif Lampung, 2024)
The media length line board is a media or facility that will be developed in development research using the R&D method using the 4D Model. This unit length line board media is targeted at grade IV elementary school students. With Learning Media as a means for students to carry out learning activities, it can also increase and hone students' creative thinking when using this board media as a tool to solve the problems they are facing. This unit length line board media is a concrete media that was developed as a form of interaction between fellow students, looking at the situation in the last two years where students are faced with digital and currently development research is being researched by the author to provide another opportunity for students to interact and learn while playing. Moreover, this media is available for elementary school students.